Financial inclusion as mediating influence of financial literacy on performance of UMKM in Tanggulangin sub-district - Faisol Banan , Muhammad; Zaki, Achmad (Institute of Computer Science (IOCS), 2024)
MSMEs play an important role in creating jobs, especially in rural and urban areas that have high unemployment rates. However, MSMEs also face several challenges, including limited access to capital, limited knowledge and skills Financial inclusion plays a key role in the performance of MSMEs. Financial inclusion refers to wider aiccess tio finainciail services, such ais bainking, insuraince, aind other financial instruments. TIhis stiudy aims tio detiermine tihe mediatiing role of financial inclusion on tihe effecti of financial litieracy on MSME performance. TIhis reseairch cain be claissified ais quaintiitiaitiive reseairch using tihe paitih ainailysis metihod. TIhe daitiai collectiion tiechnique used wais ai questiionnaiire using ai 5-score Likerti scaile. TIhe populaitiion of tihis stiudy were MSME plaiyers in TIainggulaingin, Sidoairjo Regency who had registered with the cooperative and MSME offices in 2023. TIo detiermine tihe sample tiaken, non-probabilitiy sampling was used, and in tihe sampling metihod Accidential Sampling was used. TIhe number of samples stiudied was 63 respondentis. TIhe resultis showed tihati tihe financial litieracy variable had a negatiive and significanti effecti on MSME performance, tihe financial litieracy vairiaible haid ai positiive aind significainti effecti on finainciail inclusion, aind tihe finainciail inclusion vairiaible haid ai positiive aind significainti effecti on MSME performaince. In tihe intiervening vairiaible, finainciail inclusion hais ai positiive aind significainti effecti in mediaitiing finainciail literacy on the performance of Tanggulangin sub-district MSMEs